Exoskeleton acceptance and its relationship to self-efficacy enhancement, perceived usefulness, and physical relief: A field study among logistics workers. (7th September 2021) - Siedl, Sandra M.; Mara, Martina
Abstract: Objective: This field study aimed to explore the effects of exoskeleton use on task-specific self-efficacy beliefs of logistics workers and to relate these effects to usefulness perceptions and technology acceptance. Background: A growing number of industrial companies have shown interest in having employees wearing exoskeletons to support their physical health. However, psychological consequences of exoskeleton use and mechanisms associated with workers' acceptance or rejection of exoskeletons are not yet sufficiently understood. Methods: A total of 31 logistics workers of a vehicle manufacturing company reported on their work-related self-efficacy, that is, how capable they felt of performing tasks related to their job well, before partaking in half-hour trials of a passive lift-assistive exoskeleton (Laevo V2.5) during their normal work. Afterward, they completed a questionnaire on their exoskeleton-supported self-efficacy and indicated how useful they found the exoskeleton, how much physical relief they felt from wearing it, and how willing they were to continue with its use. Results: Overall, wearing the exoskeleton did not lead to increased work-specific self-efficacy. However, indications of interaction effects were found between baseline self-efficacy, perceived physical relief, and perceived usefulness in such a way that workers who experienced the exoskeleton as more strain-relieving or more useful were also more likely to report a post-trial growth in their self-efficacy beliefs. A positive change in self-efficacy, in turn, was associated with a greater willingness to further use the exoskeleton at the workplace.